A Review of Diffusion Models and Their Applicability to App-based Services in India (Quest Journal of Management and Social Sciences, 2025)
Background: Diffusion models have been used for over half a century to predict the spread of innovations, products, and services in target strata. However, the applicability and relevance of diffusion models for the new age app-based consumer services have not been researched, especially in developing markets like India.Purpose: This paper identifies gaps in the two founding theories on diffusion– Rogers' Diffusion of Innovation Model and Bass' Diffusion Model concerning app-based consumer services in India, and attempts to deploy these theories on the diffusion of new-age applications.Methods: The paper critically examines the diffusion theories to extract implementation gaps in the new-age platform applications. Further, it works towards proposing a reduced form equation by including a dampener in the traditional diffusion model equation offered by Bass, which can represent the diffusion curve for app-based services and thus explain the diffusion better.Findings: A set of enablers and disablers is identified through this research, influencing the diffusion of new-age applications. Including these elements explains diffusion from the source and medium points of view.Conclusion: Enhanced understanding of the diffusion of service applications among the population shall help app-driven businesses efficiently build products that are well accepted and adopted by the target population.Keywords: Diffusion, Innovation, Diffusion of Innovation, Service Apps, On-demand ApplicationJEL Codes: O33, M31, L86, D83